2016
DOI: 10.1089/ten.tec.2015.0223
|View full text |Cite
|
Sign up to set email alerts
|

AnIn VitroInvestigation of Platelet-Rich Plasma-Gel as a Cell and Growth Factor Delivery Vehicle for Tissue Engineering

Abstract: Platelet-rich plasma (PRP) has been used for different applications in human and veterinary medicine. Many studies have shown promising therapeutic effects of PRP; however, there are still many controversies regarding its composition, properties, and clinical efficacy. The aim of this study was to evaluate the influence of different platelet concentrations on the rheological properties and growth factor (GF) release profile of PRP-gels. In addition, the viability of incorporated bone marrow-derived human mesen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 57 publications
(62 reference statements)
4
55
0
Order By: Relevance
“…Next to the fact that all platelet-derived products are subject of large donor variation [3], this represents a major hurdle in comparing different studies and ultimately drawing conclusions on the efficacy of PRP in these approaches. This is also highlighted in a recent study systematically investigating the influence of different platelet concentrations on both the release of growth factors and cells incorporated in PRP gels [8]. This work demonstrated that the concentration of released growth factors is strongly correlated with the platelet concentration.…”
Section: Prp In Tissue-engineered Constructsmentioning
confidence: 59%
See 4 more Smart Citations
“…Next to the fact that all platelet-derived products are subject of large donor variation [3], this represents a major hurdle in comparing different studies and ultimately drawing conclusions on the efficacy of PRP in these approaches. This is also highlighted in a recent study systematically investigating the influence of different platelet concentrations on both the release of growth factors and cells incorporated in PRP gels [8]. This work demonstrated that the concentration of released growth factors is strongly correlated with the platelet concentration.…”
Section: Prp In Tissue-engineered Constructsmentioning
confidence: 59%
“…Upon activation, PRP forms a soft hydrogel as determined in a recent rheology study [8]. As such, it represents a suitable material for soft tissue repair.…”
Section: Prp In Tissue-engineered Constructsmentioning
confidence: 92%
See 3 more Smart Citations